2014
DOI: 10.1093/eurheartj/ehu275
|View full text |Cite
|
Sign up to set email alerts
|

Changes in 24 h ambulatory blood pressure and effects of angiotensin II receptor blockade during acute and prolonged high-altitude exposure: a randomized clinical trial

Abstract: Ambulatory blood pressure increases progressively with increasing altitude, remaining elevated after 3 weeks. An angiotensin receptor blockade maintains blood pressure-lowering efficacy at 3400 m but not at 5400 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
103
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 27 publications
16
103
1
15
Order By: Relevance
“…41 Conversely, telmisartan lost its ability to reduce BP during prolonged exposure to very HA, likely because of the above reported suppression of RAAS. 24 In line with these findings, we also observed no difference in parameters reflecting viscoelastic properties of large arteries, such as PWV and other variables obtained from pulse wave analysis, including subendocardial oxygen supply and demand ratio, between telmisartan-treated and untreated subjects at any altitude. Thus, our study provides unequivocal and novel evidence on the fact that RAAS does not play any relevant role in explaining arterial wall-property changes during acute and prolonged exposition at very HA.…”
Section: Raas and Hemodynamic Changes At Hasupporting
confidence: 87%
See 3 more Smart Citations
“…41 Conversely, telmisartan lost its ability to reduce BP during prolonged exposure to very HA, likely because of the above reported suppression of RAAS. 24 In line with these findings, we also observed no difference in parameters reflecting viscoelastic properties of large arteries, such as PWV and other variables obtained from pulse wave analysis, including subendocardial oxygen supply and demand ratio, between telmisartan-treated and untreated subjects at any altitude. Thus, our study provides unequivocal and novel evidence on the fact that RAAS does not play any relevant role in explaining arterial wall-property changes during acute and prolonged exposition at very HA.…”
Section: Raas and Hemodynamic Changes At Hasupporting
confidence: 87%
“…Changes in plasma noradrenaline, renin, serum angiotensin, and aldosterone levels in both treatment groups throughout the study have been shown in detail in a previous study of ours focusing on ambulatory BP. 24 In brief, type-1 angiotensin II receptor blocker induced, as expected, a significant increase in angiotensin II (P=0.001) and renin (P=0.003) plasma values at SL, although all these variables were significantly reduced under acute exposure to 5400 m (P<0.001), with a tendency to increase again after 2 weeks at this altitude. In the placebo group, angiotensin II, renin, and aldosterone were significantly The Lake Louise score was ≥3 (considered as indicative of acute mountain sickness) in 9 subjects at Namche, in 22 subjects at BC1, and in 3 subjects at BC2.…”
Section: Highcare Project: Effect Of Type-1 Angiotensin II Receptor Bsupporting
confidence: 65%
See 2 more Smart Citations
“…According to the study of Luks (2007), no clear mechanisms explaining the increased blood pressure at high altitudes and further, guidelines or patient-centered strategies to control patients with hypertension at high altitudes are not well accepted. In their study, Parati et al (2014) showed that treatment using the angiotensin receptor blocker telmisartan led to a minor decrease in the 24 h ambulatory BP at 3400 m altitude, but had no effect on BP at 5400 m altitude. We think that these findings are important and could have impacts on the choice of antihypertensive treatment during travel to high altitude.…”
Section: Introductionmentioning
confidence: 99%